Formation and speciation of chlorinated, brominated, and iodinated haloacetamides in chloraminated iodide-containing waters. (15th November 2018) - Fang, Chao; Krasner, Stuart W.; Chu, Wenhai; Ding, Shunke; Zhao, Tiantao; Gao, Naiyun
Abstract: Haloacetamides (HAMs), an emerging class of disinfection by-products, have received increasing attention due to their elevated cyto- and genotoxicity. However, only limited information is available regarding the iodinated analogues. This study investigated the formation and speciation of iodinated haloacetamides (I-HAMs) and their chlorinated/brominated analogues during the chloramination of bromide and/or iodide-containing waters and a model compound solution over various time periods. The rapid formation of diiodoacetamide (DIAM) was observed during chloramination of three simulated samples, whereas brominated (Br-HAMs) and chlorinated haloacetamides (Cl-HAMs) increased slowly with increasing reaction time. To further understand the differences in the formation of HAMs containing different halogens, experiments with the model compound asparagine in the presence/absence of iodide were conducted. Moreover, iodine utilisation factors and iodine incorporation factors were observed to increase significantly faster and were substantially higher than those of bromine. This implied that, compared with bromide, iodide has substantially greater potential to be transformed to the corresponding HAMs during chloramination, similar to that of other classes of DBPs. That is, I-HAMs formed faster than the other species investigated, including Cl-HAMs and Br-HAMs, in the early reaction stages (0–3 h). The effect of the bromide/iodide ratio (i.e., constant iodide, increasing bromide) on I-HAM formation was also examined. With increasing bromide/iodide ratio, the formation of Br-HAMs increased and dichloroacetamide decreased, but the formation of DIAM was largely unchanged. This was consistent with the constant level of iodide in spite of the increasing bromide. Chlorine and ammonia are applied separately during chloramination in water treatment, so the effect of pre-chlorination (before adding ammonia) on the formation and speciation of I-HAMs during in situ chloramination was also evaluated. Effective mitigation of DIAM formation with in situ chloramination was achieved, and the efficiency improved with increasing pre-chlorination time, where iodide was oxidised to iodate. The HAM-associated cytotoxicity was calculated to determine the change in toxicity at different reaction times, bromide/iodide ratios, and pre-chlorination times. A similar trend as the formation of I-HAMs was observed, which increased rapidly in the first 3 h, but decreased somewhat subsequently. When the bromide/iodide ratio and pre-chlorination time was increased, the calculated toxicity of the HAMs increased (due to more formation of Br-HAMs and less Cl-HAMs) and decreased (due to less DIAM formation), respectively. Graphical abstract: Image 1 Highlights: I-HAMs formed faster than Cl- and Br-HAMs during the early stages of chloramination. Cl-HAMs shifted to Br-HAMs with increasing bromide, but DIAM was largely unchanged. Effective mitigation of DIAM formation was achieved by pre-chlorination. HAM-associated cytotoxicity was mostly driven by the concentration of I-HAMs.